2015
DOI: 10.3111/13696998.2015.1099538
|View full text |Cite
|
Sign up to set email alerts
|

Real-world evaluation of TNF-inhibitor utilization in rheumatoid arthritis

Abstract: Real-world TNFi discontinuation/switching rates correspond to randomized controlled trial non-response rates. TNFi cycling is common and associated with an increased likelihood of switching to third-line bDMARD. Switching to non-TNFi bDMARDs was associated with higher costs, mostly attributed to in-office administrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 49 publications
(47 reference statements)
2
28
1
Order By: Relevance
“…Switching rates in the study by Howe et al [13] ranged from 2.8% to 9.2% for ADA and 0% to 20% for IFX across these disease states [13]. Similar proportions of patients receiving ADA and IFX switched therapies during the first 12 months, which was comparable with the 15.4% rate of patients with RA switching that was observed in the study by Harnett et al [15]. A study of patients with UC by Rubin et al [16] showed similar rates of switching for ADA (10.5%) and IFX (9.4%) compared with our data; discontinuation rates were, however, lower at 0% and 13.3%, respectively, compared with data presented here.…”
Section: Discussionsupporting
confidence: 76%
“…Switching rates in the study by Howe et al [13] ranged from 2.8% to 9.2% for ADA and 0% to 20% for IFX across these disease states [13]. Similar proportions of patients receiving ADA and IFX switched therapies during the first 12 months, which was comparable with the 15.4% rate of patients with RA switching that was observed in the study by Harnett et al [15]. A study of patients with UC by Rubin et al [16] showed similar rates of switching for ADA (10.5%) and IFX (9.4%) compared with our data; discontinuation rates were, however, lower at 0% and 13.3%, respectively, compared with data presented here.…”
Section: Discussionsupporting
confidence: 76%
“…17 Several US studies using different methods estimated that 7.8% to 15.4% of patients switched to a second biologic DMARD within 1 year after initiating use of their first biologic DMARD. 18,[24][25][26][27] As the number of biologic DMARDs approved to treat RA increases, the selection of subsequent biologic DMARDs becomes increasingly challenging. 28 For instance, the 2013 EULAR guidelines recommend a second biologic DMARD be started if no improvement is observed within 3 months or the treatment goal is not achieved within 6 months after initiating use of the first biologic DMARD.…”
Section: Discussionmentioning
confidence: 99%
“…Another real-world study recently examined treatment patterns among patients who initiated treatment with a TNFi in 2011 or 2012, including 764 patients who switched to a different targeted DMARD 7. The probability of switching again was significantly greater for TNFi cyclers compared with non-TNFi switchers (37% vs 28%; P =0.031).…”
Section: Discussionmentioning
confidence: 99%